Novelties from the Serra Nova State Park (Minas Gerais, Brazil): two new endemic species of Eriocaulaceae - Echternacht, Livia; Watanabe, Maurício Takashi Coutinho; Andrino, Caroline Oliveira (Phytotaxa, 2021)
Two new micro-endemic species of Eriocaulaceae are described from the Campos Rupestres of Serra Nova State Park, a conservation unit located in the Espinhaço Range in northern Minas Gerais state, Brazil. Herein we provide descriptions, illustrations, photographs and maps, together with notes on morphology, distribution, phenology, taxonomy, and conservation. Paepalanthus ferrugineus is distinguished mainly by the reddish-brown involucral bracts, surpassing the floral disc, with the apex attenuate and tufted adaxially, tufted sepals and hairy petals. Syngonanthus polyaxis is easily differentiated by the inflorescence architecture with three morphologically distinct axial parts. Both species are considered Critically Endangered according to the IUCN Red List criteria.